2010
DOI: 10.1007/s00421-010-1424-8
|View full text |Cite
|
Sign up to set email alerts
|

Yearlong physical activity and sarcopenia in older adults: the Nakanojo Study

Abstract: We tested the hypothesis that a low level of regular daily physical activity in elderly individuals would be associated with a clinically significant degree of sarcopenia. Subjects were 78 male and 97 female free-living Japanese, aged 65-84 years. A pedometer/accelerometer measured continuously the number of steps taken and the intensity of activity 24 h/day for 1 year. A whole-body dual X-ray absorptiometry scan assessed skeletal muscle mass in the upper and lower extremities at the end of the year. Sarcopeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
116
2
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(133 citation statements)
references
References 32 publications
13
116
2
2
Order By: Relevance
“…In the last decade, there have been a limited number of studies that examined the relationship between accelerometer-(or pedometer-) determined daily ambulatory activity and skeletal muscle size. In those studies, the data were collected from middle-aged and older populations (50 -84 years old), with daily activities greater than 3 METs considered to be important for muscular adaptation 49,50) . Studies using dual energy X-ray absorptiometry (DXA), which estimates the lean tissue mass of the entire lower limb, however, produced mixed results as to the efficacy of daily ambulatory activity on muscle hypertrophy.…”
Section: Muscle Hypertrophy With Endurance Trainingmentioning
confidence: 99%
“…In the last decade, there have been a limited number of studies that examined the relationship between accelerometer-(or pedometer-) determined daily ambulatory activity and skeletal muscle size. In those studies, the data were collected from middle-aged and older populations (50 -84 years old), with daily activities greater than 3 METs considered to be important for muscular adaptation 49,50) . Studies using dual energy X-ray absorptiometry (DXA), which estimates the lean tissue mass of the entire lower limb, however, produced mixed results as to the efficacy of daily ambulatory activity on muscle hypertrophy.…”
Section: Muscle Hypertrophy With Endurance Trainingmentioning
confidence: 99%
“…Exercise and fitness activities including team sports make up a greater proportion of total moderate or vigorous physical activity time in young adults, whereas domestic activities make up a greater proportion of total moderate/vigorous physical activity time in older adults (Belanger et al 2011). These daily physical activities include sports that are highly dependent upon age-related changes in skeletal muscle mass (Park et al 2010;Abe et al 2012b). A limited number of studies have reported that the electromyogram activity patterns during daily activities differed between muscle groups located in the anterior and posterior aspects of the limbs (Sawai et al 2006;Shiraiwa et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Levels of physical activity were classified by a semi-structured interview that contained questions about the type, frequency, duration and intensity of physical activity during the six months prior to the study. These conflicting results may be due to the limitation of the instruments used to measure habitual physical activity, as questionnaires are difficult to apply in this population, as short and long term memory are limited, and cognitive loss is also common (Park et al, 2010;Shephard, 2003). Moreover, it emphasizes that different types of questionnaires may have distinct cut-off points to categorize a subject as active or not, when compared to other questionnaires, and this fact can also influence the results.…”
Section: Discussionmentioning
confidence: 99%
“…The literature contains few studies that have analyzed the relationship between physical activity practice and lean body mass (Buonani et al, 2013;Park, Park, Shephard, & Aoyagi, 2010), and in addition, there are a lack of studies that have investigated these aspects in menopausal women using accurate instruments to measure physical activity.…”
Section: Introductionmentioning
confidence: 99%